2018
DOI: 10.1186/s13075-018-1629-5
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analysis to understand genetic relationships between habitual coffee intake and gout

Abstract: BackgroundIncreased coffee intake is associated with reduced serum urate concentrations and lower risk of gout. Specific alleles of the GCKR, ABCG2, MLXIPL, and CYP1A2 genes have been associated with both reduced coffee intake and increased serum urate in separate genome-wide association studies (GWAS). The aim of this study was to determine whether these single nucleotide polymorphisms (SNPs) influence the risk of gout through their effects on coffee consumption.MethodsThis research was conducted using the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…29 Furthermore, another locus associated with urinary sodium, MLXIPL, has been associated with reduced serum uric acid concentrations and consequently a lower risk of gout, but also with increased coffee consumption. 30 Multiple studies have reported that increased coffee consumption is associated with reduced serum uric acid concentrations 31 and lower risk of developing gout. 32,33 This association has been attributed to several potential mechanisms including improved insulin resistance 34 and caffeine-mediated inhibition of xanthine oxidase.…”
Section: Novel Biologymentioning
confidence: 99%
“…29 Furthermore, another locus associated with urinary sodium, MLXIPL, has been associated with reduced serum uric acid concentrations and consequently a lower risk of gout, but also with increased coffee consumption. 30 Multiple studies have reported that increased coffee consumption is associated with reduced serum uric acid concentrations 31 and lower risk of developing gout. 32,33 This association has been attributed to several potential mechanisms including improved insulin resistance 34 and caffeine-mediated inhibition of xanthine oxidase.…”
Section: Novel Biologymentioning
confidence: 99%
“…Gout is a kind of hyperuricemia caused by the increased synthesis or decreased excretion of uric acid due to the disorder of purine metabolism (Hutton et al 2018). When the level of uric acid in blood is too high, uric…”
Section: Discussionmentioning
confidence: 99%
“…Gout is a kind of hyperuricemia caused by the increased synthesis or decreased excretion of uric acid due to the disorder of purine metabolism (Hutton et al 2018). When the level of uric acid in blood is too high, uric acid is deposited in joints, soft tissues, cartilages and kidneys in the form of sodium salts, causing in ammatory reaction of tissues (Vazquezmellado et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of ALDH therefore may affect gout independently of coffee consumption. Furthermore, Hutton et al reported that the risk alleles of GCKR and MLXIPL affect gout independently of coffee intake ( 10 ). Based on these facts, we removed rs671 ( ALDH2 ), rs1260326 ( GCKR ), and rs13234378 ( MLXIPL ) from 10 instruments and reanalyzed using the remaining seven instruments.…”
Section: Methodsmentioning
confidence: 99%